2017
DOI: 10.1016/j.devcel.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

APC/CFzr/Cdh1-Dependent Regulation of Planar Cell Polarity Establishment via Nek2 Kinase Acting on Dishevelled

Abstract: The Anaphase Promoting Complex/Cyclosome (APC/C) is an E3 ubiquitin ligase, well known for its role in cell cycle progression. However, it has been linked to additional functions, mainly in neuronal contexts, when using the co-activator Cdh1/Fzr. Here, our data indicate a post-mitotic requirement for the APC/CFzr/Cdh1 in epithelial cell patterning and planar cell polarity (PCP) in Drosophila. PCP signalling is critical for development by establishing cellular asymmetries and orientation within the plane of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…KEGG and GO enrichment analyses were conducted and revealed that NEK2 was mainly enriched in cell cycle and mitosis-related pathways. Many studies have suggested that NEK2 is a kinase implicated in regulating the S/G2 phase in cell cycle (Pfleger and Kirschner, 2000;Weber and Mlodzik, 2017). Notably, NEK2 is involved in the separation of centrosomes.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG and GO enrichment analyses were conducted and revealed that NEK2 was mainly enriched in cell cycle and mitosis-related pathways. Many studies have suggested that NEK2 is a kinase implicated in regulating the S/G2 phase in cell cycle (Pfleger and Kirschner, 2000;Weber and Mlodzik, 2017). Notably, NEK2 is involved in the separation of centrosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, APC/C Fzr regulates the transition from mitosis into endoreplication cycles in the Drosophila salivary gland, leading to the formation of polytene chromosomes (Zielke et al, 2008). Besides its well-known function during mitosis, the APC/C has been shown to also have essential cell-cycle-independent roles (for example, see Braun et al, 2018 preprint;Martins et al, 2017;Meghini et al, 2016;Neuert et al, 2017;Silies and Klämbt, 2010;van Roessel et al, 2004;Weber and Mlodzik, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the fruit fly, different postmitotic roles have been described for the APC/C. It controls synaptic size via the downstream effector Liprin-alpha at the larval neuromuscular junction, acts during the establishment of planar cell polarity and functions in neurons of the embryonic peripheral nervous system (PNS) to control glial migration (Silies and Klämbt, 2010;van Roessel et al, 2004;Weber and Mlodzik, 2017). As mentioned above, Drosophila peripheral glial cells migrate along the axons of the motoneurons, which are decorated with a gradient of the Ig-domain cell-adhesion molecule Fasciclin 2 (Fas2).…”
Section: Introductionmentioning
confidence: 99%